Level of Passing Skills in and Outside Football of Extracurricular Participants of State Junior High School 2 Martapura - M. Royhan; Mita Erliana; Ramadhan Arifin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of the study was to find out how well the Passing Skill Level in and outside football in the Extracurricular Participants of the State Junior High School 2 Martapura. The research method is a quantitative descriptive research with a football passing skill measurement test. Research on the Level  of Passing Skills in and Outside Football of Extracurricular Participants of State Junior High School 2 Martapura with a measurement test of inside and outside passing skills tests. The total population of 40 extracurricular participants and the technique used to determine the sample with the purposive sampling technique  (who are willing to be samples), the number of samples in this study is 18 extracurricular participants. The results of the research The level of passing skills in the extracurricular participants of the State Junior High School 2 Martapura was very good in the category 0 (0%), good 0 (0%), medium 0 (0%), Less 2 (11%), less than 16 (89%). The results of the study The level of passing skills outside the extracurricular participants of the State Junior High School 2 Martapura category is very good 0 (0%), good 0 (0%), medium (0%), less than 0 (0%), less than 18 (100%). Conclusion of the research results The level of passing skills inside and outside of the extracurricular participants of the State Junior High School 2 Martapura is a category of less than once.